Análise da gestão estratégica de custos no setor de aviação comercial brasileiro - Miotto, Genossi Rauch (Universidade do Vale do Rio do Sinos, 2007)
This work analyzes the impacts of the strategic decisions in costs and in the attainment of the operational result of the Brazilian commercial aviation companies through techniques of strategic cost management. The applied techniques in this study were the costs drivers and target cost. Through a descriptive and documental research, the data of the passengers’ transport operations of the main domestic aerial companies were analyzed quantitatively and qualitatively from 1997 to 2005. The analysis of the goal-cost allowed identifying the transformations in the companies’ business model mainly in cost and tariffs. Incoming companies inserted such transformations during the analyzed period. It made the already established companies to adopt adaptation strategies. Some succeeded and other simply failed, abandoning the market. Through the structural cost driver “technology” one analyzed the profile of the companies’ fleet of aircrafts, in that one identified the relationship with two of the main costs, cost with fu
Keywords: ambiente competitivo; aviação comercial; custos; gestão estratégica; commercial aviation; competitive context; costs; strategic administration; Ciências Sociais Aplicadas